DESENTRALISASI” PENYIARAN TELEVISI DI INDONESIA DALAM KERANGKA HUKUM - Nyoman Septiari, I Gusti Ayu; Sunarto, Sunarto; Nugroho, Adi (Interaksi Online, 2024)
During the reform era, the word “decentralization” was often associated with the television broadcasting system in Indonesia. Decentralization is the transfer of responsibility from the ruler at the center to a lower unit. However, in the broadcasting industry, the concept of decentralization is also often associated with the network station system in Law Number 32 of 2002 concerning Broadcasting. This research aims to find the meaning of decentralization contained in the legal framework regarding broadcasting, namely in Law Number 32 of 2002 concerning Broadcasting and Law Number 11 of 2020 concerning Cipta Kerja. The method used in this study is Wilhelm Dilthey hermeneutic analysis through five analysis techniques, namely grammatical analysis, semantic analysis, and text meaning analysis. The word "decentralization" does not appear explicitly in the regulation regarding broadcasting. However, this study found that the meaning of decentralization appears implicitly in Law Number 32 of 2002 concerning Broadcasting and Law Number 11 of 2020 concerning Cipta Kerja. Broadcasting decentralization appears in regulation that discuss KPI Daerah at the regional level, the establishment of network station systems, ownership and control, and the ideology contained in the two laws. This study finds that the meaning of broadcasting decentralization is not only contained in the regulations regarding the network station system, but also in the regulation regarding KPI, ownership and control, broadcast content, and broadcasting licensing. However, in its development and implementation, these regulations do not run as they should in the broadcasting industry in Indonesia. This is because the existing regulations have not expressly regulated the decentralization of broadcasting, thus providing a loophole for broadcasting operators not to implement these regulations. As a result, the broadcasting industry in Indonesia is increasingly centralized, especially in terms of bureaucracy regulated in business licensing Article 72 number 3 of the Cipta Kerja Law. Negative implications not only appear in the field of bureaucracy, but also result in the centralization of ownership and broadcast content that ignores local interests.